THE EFFECT OF ACCOUNT REPRESENTATIVE PERFORMANCE, SELF ASSESSMENT SYSTEM, AND TAX SERVICE QUALITY ON TAXPAYER COMPLIANCE (Empirical Study of Individual Taxpayers on KP2KP Sidrap) - Sri Dewi Puspitasari; Muhammad Asdar; Musran Munizu (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
Indonesia has made various efforts to optimize all types of revenue as a source of state revenue that is used to finance all public interests, one of which is needed and most important is the active participation of its citizens to contribute to the country in the form of taxes so that all development needs can be financed. Taxes are compulsory contributions to the state that are owned by private persons or entities that are compelling based on law, without receiving direct compensation, and are used for state needs for the greatest prosperity of the people. The purpose of this study was to analyze the effect of account representative performance, self-assessment system, and service quality on individual taxpayer compliance at KP2KP Sidrap. This research is a quantitative study by taking samples, namely individual taxpayers who are registered at KP2KP, considering that there are quite a lot of taxpayers, the Slovin formula is used so that the total sample size is 98 respondents. The data collection technique is through observation and questionnaires, while the data analysis technique uses multiple linear regression analysis. The findings show that the performance of the Account Representative has a significant effect on taxpayer compliance at KP2KP Sidrap. Self Assessment System has a significant effect on taxpayer compliance at Sidrap KP2KP, and the quality of Tax Service has a significant effect on taxpayer compliance at KP2KP Sidrap.